Comparison of protein variations in Thlaspi caerulescens populations from metalliferous and non-metalliferous soils - Visioli, Giovanna; Pirondini, Andrea; Malcevschi, Aliosha; Marmiroli, Nelson (International journal of phytoremediation, 2010)
In this work we analysed the protein variations which occurred in two Thlaspi caerulescens populations when subjected to 0 and 10 microM nickel (Ni) treatments: the Ni hyperaccumulator T. caerulescensfrom a metalliferous soil in Italy and T. caerulescens from Czech Republic, adapted to grow on a non-metalliferous soil. Ni accumulation in roots and shoots and the effect on growth and morphology were examined. Leaves proteins profiles of Ni treated and untreated samples were analysed by two dimensional liquid chromatography technique. From the comparison of more than 500 proteins, few differences were observed between treated and untreated plants of the same population. Differences were found between the two Thlaspi populations, instead. Proteins involved in transport, metal chelation, and signal transduction increased in abundance in the 10 microM Ni treated samples while, in condition of absence of Ni, proteins involved in sulphur metabolism, protection against reactive oxygen species and stress response showed to increase in abundance in the two populations. These proteins can be used as biomarkers both for monitoring biodiversity in indigenous plants and for selection of Ni phytoremediation plants.
Keywords: genetická variace; kořeny rostlin; Genetic Variation; Enzymes; Plant Roots; Nickel; enzymy; Soil; Plant Proteins; regulace genové exprese u rostlin; rostlinné proteiny; kovy; Czech Republic; Česká republika; thioredoxiny; Metals; Italy; listy rostlin; Plant Leaves; nikl; půda; Gene Expression Regulation, Plant; Itálie; Thlaspi; Thioredoxins